Rapid structural characterisation of benzylisoquinoline and aporphine alkaloids from Ocotea spixiana acaricide extract by HPTLC‐DESI‐MSn. Issue 6 (15th April 2020) - Conceição, Rodrigo S.; Reis, Isabella M.A.; Cerqueira, Amanda P.M.; Perez, Consuelo J.; Junior, Manoelito C. dos Santos; Branco, Alexsandro; Ifa, Demian R.; Botura, Mariana B.
Abstract: Introduction: Lauraceae alkaloids are a structurally diverse class of plant specialised secondary metabolites that play an important role in modern pharmacotherapy, being useful as well as model compounds for the development of synthetic analogues. However, alkaloids characterisation is challenging due to low concentrations, the complexity of plant extracts, and long processes for accurate structural determinations. Objective: The use of high‐performance thin layer chromatography coupled with desorption electrospray ionisation multistage mass spectrometry (HPTLC DESI‐MS n ) as a fast tool to identify alkaloids present in Ocotea spixiana extract and evaluate the extract's acaricide activity. Methods: Ocotea spixiana twigs were extracted by conventional liquid–liquid partitioning. HPTLC analysis of the ethyl acetate extract was performed to separate isobaric alkaloids prior to DESI‐MS n analysis, performed from MS 3 up to MS 7 . The extract's acaricide activity against Rhipicephalus microplus was evaluated by in vitro (larval immersion test) and in silico tests. Results: HPTLC‐DESI‐MS n analysis was performed to identify a total of 13 aporphine and four benzylisoquinoline‐type alkaloids reported for the first time in O. spixiana. In vitro evaluation of the extract and the alkaloid boldine showed significant activity against R. microplus larvae. It was established in silico that boldine had important intermolecular interactions with R. microplus acetylcholinesterase enzyme. Conclusion: The present study demonstrated that HPTLC‐DESI‐MS n is a useful analytical tool to identify isoquinoline alkaloids in plant extracts. The acaricide activity of the O. spixiana ethyl acetate extract can be correlated to the presence of alkaloids. Abstract : ‐HPTLC‐DESI‐MSn is a useful fast tool to identify alkaloids from plant extracts. ‐19 alkaloids (13 aporphine and 4 benzylisoquinoline alkaloids) were detected in the Ocotea spixiana extract. ‐ Alkaloid boldine showed in vitro acaricide activity, and established important in silico interactions with R. microplus AChE